2019
DOI: 10.1155/2019/2573873
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Objective Reentrant Hybrid Flowshop Scheduling with Machines Turning on and off Control Strategy Using Improved Multi‐Verse Optimizer Algorithm

Abstract: This paper focuses on the multi-objective optimization of the reentrant hybrid flowshop scheduling problem (RHFSP) with machines turning on and off control strategy. RHFSP exhibits significance in many industrial applications, but scheduling with both energy consumption consideration and reentrant concept is relatively unexplored at present. In this study, an improved Multi-Objective Multi-Verse Optimizer (IMOMVO) algorithm is proposed to optimize the RHFSP with objectives of makespan, maximum tardiness, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Recent studies show that metaheuristics are still the preferred methods to solve the complex problem of the RFS. Recently, various metaheuristics have been developed, such as iterated greedy algorithm [27], Improved Multi-Verse Optimizer Algorithm [28]. The latest studies also indicate that the hybrid method gains more concerns, as found in the study by Amrouche et al [29] which combined a simulated annealing and lower bounds, and Lin et al [30] which proposed a hybrid harmony search and genetic algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies show that metaheuristics are still the preferred methods to solve the complex problem of the RFS. Recently, various metaheuristics have been developed, such as iterated greedy algorithm [27], Improved Multi-Verse Optimizer Algorithm [28]. The latest studies also indicate that the hybrid method gains more concerns, as found in the study by Amrouche et al [29] which combined a simulated annealing and lower bounds, and Lin et al [30] which proposed a hybrid harmony search and genetic algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…On the basis of literature studies [10,29], a bi-objective RHFSP mathematical model is proposed in this paper. Formulas (1) and (2) represent the two objective functions.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Table1. Researches on RFSS problem up to 2021 [15,16] In this subsection, the different models of RFSS are reviewed and classified into three aforementioned groups. In the lowest class, many works on single objective RFSS were done without using the important parameters such as sequence-dependent setup time or release date [17][18][19]5,20,21,4,22].…”
Section: Introductionmentioning
confidence: 99%